Maternal contribution to the reproductive potential of a recovering fish stock: variability in the fecundity and condition of haddock (Melanogrammus aeglefinus) on the Scotian Shelf - Julia Blanchard (2000)
The maternal contribution to the reproductive potential of a fish stock can be assessed by measuring the fecundity and condition of adult females. In turn, this can provide a more accurate measure of potential egg production than traditional estimates of Spawning Stock Biomass (SSB). This study represents the first comprehensive evaluation of the reproductive potential of the Eastern Scotian Shelf (ESS) haddock ( Melanogrammus aeglefinus ) stock. Three years of fecundity data were collected over the period 1997-1999 for the Eastern Scotian Shelf haddock and data were also collected for the neighbouring, Southwest Scotian Shelf haddock stock in 1998 and 1999. Fecundity-body size relationships were determined for the three years of data collected and were highly variable compared to the neighbouring southwestern Scotian Shelf stock. Significant inter-annual differences in the intercepts of these relationships were observed over the 1997-1999 period and appeared to be reflective of inter-annual differences in condition. Relative to other haddock stocks throughout the North Atlantic, ESS haddock exhibited the lowest and most variable fecundity-length relationship. Multiple regression models incorporating length and condition were developed using three different measures of condition: liver index (H.S.I.); Fulton’s condition index (K) and length specific weight (with a length*weight interaction term). All measures of condition contributed to explaining additional variation in fecundity-at-length (from 15- 19%). H.S.I. explained the most variation, followed by length specific weight, then Fulton’s K. The stock reproductive potential was reconstructed for a two decade period (1979-1999) by incorporating the fecundity equations into a length based population model. This yielded annual estimates of Total Egg Production (TEP). Results showed that TEP has declined over that period with evidence of a recent increase in 1999. The decline was more drastic when TEP was separated for repeat spawners (fish above 40.5 cm). Also, ...